(untitled) (Research, Society and Development, 2026)
The aim of this study is to analyze the main challenges and advances in gynecological cytology in the context of cervical cancer screening and prevention. The methodology adopted was a literature review, with a quantitative and descriptive approach, based on the analysis of 16 national and international studies published between 2019 and 2025. The sources were obtained from the SciELO, PubMed, LILACS, and Virtual Health Library (VHL) databases. The results demonstrate that, despite technical advances—such as liquid-based cytology, the use of biomarkers, and automation—the Pap smear test is still not equitably accessible to Brazilian women. Factors such as low education levels, reduced income, lack of educational campaigns, fragile health services, and discontinuity of care were associated with lower adherence to preventive examinations, especially in riverside, peripheral, and low-income populations. HPV vaccination, although effective, still faces low coverage in vulnerable regions. In this context, prevention strategies must go beyond the technical dimension, incorporating territorial, educational, and intersectoral actions. It is concluded that the success of cervical cancer screening depends on overcoming the social and structural barriers that still limit the effectiveness of gynecological cytology in Brazil. Public policies sensitive to the reality of women, accompanied by investment in professional training, health education, and strengthening of primary care, are fundamental to transforming scientific advances into accessible and universal care practices.